UPAYA MENINGKATKAN MINAT MENULIS KARYA ILMIAH MELALUI KEGIATAN IN HOUSE TRAINING PADA GURU DI SD NEGERI RINGINPUTIH 2 - Sumarsih, Eni (Jurnal Inovasi Pendidikan dan Teknologi Informasi (JIPTI), 2023)
The reality on the ground shows that teacher professionalism is still lacking. Efforts to improve teacher professionalism can be done through writing scientific papers. However, in terms of quality what is expected of someone who has an interest in writing scientific papers is still far from expectations. Based on the results of initial observations conducted by researchers through supervision, out of 8 teachers, only 3 teachers were interested in writing excellent scientific papers. To overcome this problem, school action research (PTS) was carried out through In House Training activities. The purpose of this study was to increase interest in writing scientific papers for teachers at SD Negeri Ringinputih 2 in the academic year 2022/2023. The subjects of this study were teachers at SD Negeri Ringinputih 2, Borobudur District, totaling 8 people. The research data sources were obtained from qualitative data in the form of data from observations of teacher activities and quantitative data in the form of data on the results of an interest in writing scientific work assessments. The results of the first cycle of research obtained an average percentage of achievement in making PTK 58.4% and Best Practice 61.3%. While the results of the second cycle of research experienced an average increase in the percentage of achieving PTK 95.8% and Best Practice 100%. Based on the results of this research, In House Training Activities can increase interest in writing scientific papers for teachers at SD Negeri Ringinputih 2 for the 2022/2023 academic year.